2016
DOI: 10.1523/jneurosci.3475-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

Catecholamine-Mediated Increases in Gain Enhance the Precision of Cortical Representations

Abstract: Neurophysiological evidence suggests that neuromodulators, such as norepinephrine and dopamine, increase neural gain in target brain areas. Computational models and prominent theoretical frameworks indicate that this should enhance the precision of neural representations, but direct empirical evidence for this hypothesis is lacking. In two functional MRI studies, we examine the effect of baseline catecholamine levels (as indexed by pupil diameter and manipulated pharmacologically) on the precision of object re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
64
3
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(76 citation statements)
references
References 46 publications
8
64
3
1
Order By: Relevance
“…For example, changes in pupil responses correspond to changes in locus coeruleus firing rate (Joshi et al, 2016;Murphy et al, 2014;Varazzani et al, 2015), as well as norepinephrine concentrations (Phillips et al, 2000;Warren et al, 2016). Extending recent work (Chmielewski et al, 2017;Dippel et al, 2017;Mückschel et al, 2017), we found that midfrontal theta correlated with pupil dilation responses, suggesting that the mPFC and LC-NE might interact to resolve conflict and respond to surprising events even during choices based on personal preferences.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…For example, changes in pupil responses correspond to changes in locus coeruleus firing rate (Joshi et al, 2016;Murphy et al, 2014;Varazzani et al, 2015), as well as norepinephrine concentrations (Phillips et al, 2000;Warren et al, 2016). Extending recent work (Chmielewski et al, 2017;Dippel et al, 2017;Mückschel et al, 2017), we found that midfrontal theta correlated with pupil dilation responses, suggesting that the mPFC and LC-NE might interact to resolve conflict and respond to surprising events even during choices based on personal preferences.…”
Section: Discussionsupporting
confidence: 80%
“…Further, enhanced midfrontal theta and pupil responses might reflect dynamic switching between brain networks (Cocchi et al, 2013;Uddin, 2015). For example, past work suggests that pupil responses correlate strongly with LC-NE system activity (Aston-Jones and Cohen, 2005b; Murphy et al, 2014;Rajkowski et al, 1994), and this neuromodulatory system may be involved in resetting networks and optimizing behavior (Bouret and Sara, 2005;Nieuwenhuis et al, 2005;Sara and Bouret, 2012;Urai et al, 2017;Usher et al, 1999;Warren et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…1) performed the motion discrimination task optimized for measurement of decision-related changes in pupil diameter. We first examined the effect of speed emphasis on unbaselined pupil diameter prior to motion onset, which has previously been used as a proxy for ‘tonic' fluctuations in neural gain4548. Consistent with a static increase in gain under greater speed pressure, this metric was larger in the DL regime than in the FR regime ( t 22 =6.9, P <1 × 10 −6 ; Fig.…”
Section: Resultsmentioning
confidence: 92%
“…The brainstem nucleus locus coeruleus exhibits a rapid increase in activity in response to salient stimuli, including task-irrelevant intense auditory stimuli (Grant, Aston-Jones, & Redmond, 1988), and the consequent phasic increase in norepinephrine release increases neural gain. In recent research, we have found that norepinephrinemediated increases in gain enhance the precision of cortical perceptual representations (Warren et al, 2016). Several researchers have proposed that the AS effect and related phasic alerting effects are mediated by phasic norepinephrine release (Fernandez-Duque & Posner, 1997;Hackley & Valle-Incl an, 1999.…”
Section: Discussionmentioning
confidence: 96%